TRADISI DAN HUKUM ADAT DALAM SISTEM PEMBAGIAN WARISAN DI MASYARAKAT MUSLIM DI DESA OELET KECAMATAN AMANUBAN TIMUR NTT - Arjun Saksena; Ersya Dwi Rahmawati; Ersya Savira Maharani; Imam Buchori; Nadya Jihan Rahayu (Pojok Publisher, 2025)
Indonesian society is known for its plural legal system, in which customary law, Islamic law, and national law coexist and interact. In Oelet Village, East Amanuban District, East Nusa Tenggara, there exists a unique inheritance practice known as Palsait Naheun, which places the eldest son as the central figure in the inheritance process. This study aims to understand how the inheritance system is implemented according to local traditions and how it differs from the provisions of Islamic inheritance law. The research employs a literature review method with a descriptive qualitative approach, analyzing scholarly sources such as journals, theses, and relevant books. The findings show that the Palsait Naheun system reflects strong patrilineal cultural values, with inheritance being symbolically given to daughters and dominated by male heirs. Although this contrasts with Islamic law, which proportionally and explicitly guarantees women's inheritance rights, the local community perceives their customary system as a form of justice based on traditional norms. However, a growing awareness of gender justice according to Islamic principles has begun to emerge among the younger generation. This study suggests the need for intergenerational dialogue and educational approaches that respect customary values while accommodating more egalitarian principles of Islamic inheritance law.